Effect of a redesigned fracture management pathway and 'virtual' fracture clinic on ED performance. Issue 6 (13th June 2014) - Vardy, J; Jenkins, P J; Clark, K; Chekroud, M; Begbie, K; Anthony, I; Rymaszewski, L A; Ireland, A J
Abstract : Objectives: Collaboration between the orthopaedic and emergency medicine (ED) services has resulted in standardised treatment pathways, leaflet supported discharge and a virtual fracture clinic review. Patients with minor, stable fractures are discharged with no further follow-up arranged. We aimed to examine the time taken to assess and treat these patients in the ED along with the rate of unplanned reattendance. Design: A retrospective study was undertaken that covered 1 year before the change and 1 year after. Prospectively collected administrative data from the electronic patient record system were analysed and compared before and after the change. Setting: An ED and orthopaedic unit, serving a population of 300 000, in a publicly funded health system. Participants: 2840 patients treated with referral to a traditional fracture clinic and 3374 patients managed according to the newly redesigned protocol. Outcome measures: Time for assessment and treatment of patients with orthopaedic injuries not requiring immediate operative management, and 7-day unplanned reattendance. Results: Where plaster backslabs were replaced with removable splints, the consultation time was reduced. There was no change in treatment time for other injuries treated by the new discharge protocol. There was no increase in unplanned ED attendance, related to the injury, within 7 days (p=0.149). There was a decrease in patients reattending the ED due to a missed fracture clinic appointment. Conclusions: This process did not require any new time resources from the ED staff. This process brought significant benefits to the ED as treatment pathways were agreed. The pathway reduced unnecessary reattendance of patients at face-to-face fracture clinics for a review of stable, self-limiting injuries.